DZIELIMY SIĘ DOŚWIADCZENIEMApplying vertical rectus abdominis muscle (VRAM) flap in surgical treatment of extensive chest wall injury after deep infection of the sternotomy wound - Kołaczkowska, Magdalena; Jankau, Jerzy; Batkiewicz, Sebastian; Michałkiewicz, Maria; Rzymski, Stanisław; Siondalski, Piotr (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2011)
Sternotomy wound infection may be a very serious, potentially fatal complication of cardiosurgical procedures. Deep infection of the wound with mediastinitis requires intensive care which involves removing the cause of infection and often reconstructing largely injured chest wall. This paper presents treatment of serious complications of sternotomy wound healing. The large chest wall defect which resulted from the multi-stage treatment caused severe respiratory failure in the patient, which required several months of mechanical ventilation. Intraoperatively, after the excision of the infected tissues and sternum bone material, the chest wall defect was filled with pedicled omentum majus flap and VRAM (vertical rectus abdominis muscle flap). The initial result of the procedure was satisfactory with a few weeks of improved respiratory functions after the surgery, when the time of self-sustained, successful breathing without the respirator was gradually prolonged. However, a few months after the procedure, the patient expired due to systemic fungal infection.